2011
DOI: 10.1007/s10803-011-1206-0
|View full text |Cite|
|
Sign up to set email alerts
|

Handwriting Difficulties in Children with Autism Spectrum Disorders: A Scoping Review

Abstract: Functional handwriting involves complex interactions among physical, cognitive and sensory systems. Impairments in many aspects of these systems are associated with Autism spectrum disorders (ASD), suggesting a heightened risk of handwriting difficulties in children with ASD. This scoping review aimed to: (1) survey the existing evidence about potential contributions to compromised handwriting function in children with ASD, and (2) map out the existing studies documenting handwriting difficulties in children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
89
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(104 citation statements)
references
References 87 publications
(133 reference statements)
5
89
0
10
Order By: Relevance
“…These speak of deficits such as in handwriting (Kushki, Chau, & Anagnostou, 2011) and (relatedly) fine-precision grip (David, Baranek, Wiesen, Miao, & Thorpe, 2012); in postural stability (Molloy, Dietrich, & Bhattacharya, 2003) and as documented in the studies above, gait (Esposito & Venuti, 2008;VernazzaMartin et al, 2005;Vilensky, Damasio, & Maurer, 1981); of akinesia, dyskinesia and bradykinesia (Damasio & Maurer,6 Motor symptoms are not the only symptoms that appear in the first year of life; we refer the interested reader to several other papers which point out early abnormalities in social orientation among other symptoms in the first year of life (Clifford & Dissanayake, 2008;Clifford et al, 2013;Clifford, Young, & Williamson, 2007;Dawson et al, 2004;Maestro, Muratori, Barbieri et al, 2001; 1978; Maurer & Damasio, 1982); and finally of hand dystonia and facial grimacing (Wing, 1981).…”
mentioning
confidence: 99%
“…These speak of deficits such as in handwriting (Kushki, Chau, & Anagnostou, 2011) and (relatedly) fine-precision grip (David, Baranek, Wiesen, Miao, & Thorpe, 2012); in postural stability (Molloy, Dietrich, & Bhattacharya, 2003) and as documented in the studies above, gait (Esposito & Venuti, 2008;VernazzaMartin et al, 2005;Vilensky, Damasio, & Maurer, 1981); of akinesia, dyskinesia and bradykinesia (Damasio & Maurer,6 Motor symptoms are not the only symptoms that appear in the first year of life; we refer the interested reader to several other papers which point out early abnormalities in social orientation among other symptoms in the first year of life (Clifford & Dissanayake, 2008;Clifford et al, 2013;Clifford, Young, & Williamson, 2007;Dawson et al, 2004;Maestro, Muratori, Barbieri et al, 2001; 1978; Maurer & Damasio, 1982); and finally of hand dystonia and facial grimacing (Wing, 1981).…”
mentioning
confidence: 99%
“…It includes the complex interaction among physical, cognitive, and sensory systems (Kushki et al 2011). Most students with autism spectrum disorder (ASD) are likely to have difficulties with written expression which will impact their academic performance across subject matter areas (Griswold et al 2002; Whitby and Mancil 2009).…”
mentioning
confidence: 99%
“…Further, ASD is also associated with differences in manual dexterity, muscle tone, and grip strength (Kushki et al 2011).…”
mentioning
confidence: 99%
“…A recently conducted scoping review on handwriting difficulties in children with Autism Spectrum Disorders, ASD, found altogether six studies, of which two specifically addressed handwriting difficulties in children with AS (10). The review concluded that diminished overall legibility and letter formulation are points of convergence among existing studies of handwriting quality in children with ASD.…”
Section: Introductionmentioning
confidence: 99%